The Emerald handbook of authentic leadership - Turcan, Romeo V.; Reilly, John E.; Mølbjerg Jørgensen, Kennenth; Taran, Yariv; Bujac, Andreea I. (Emerald handbooks., 2023)
The Emerald Handbook of Authentic Leadership is a ground-breaking interdisciplinary collection, opening the black box of leadership authenticity to advance understanding of theory and practice. It presents a wide-ranging, diverse source of new concepts, theories, insights, applications to advance thinking and practice in leadership and leadership authenticity. The first publication of its kind, the contributors - leading scholars, researchers, business and NGO leaders, policy makers - explore differing, contrasting perspectives on the evolving, fluid subject of authentic leadership. The thematic sections examine 'The Search for Authenticity from Theory to Practice', 'The Search for Authenticity from Practice to Theory', and 'Developing Authentic Leadership Values, Understanding and Practice'. The Emerald Handbook of Authentic Leadership is a quest for interdisciplinary insights arising out of theory and practice. It is intended for a wide readership interested in leadership and leadership authenticity in the contemporary world.